Kajian Al-Maṣlaḥah Al-Mursalah Terhadap Pemenuhan Legalitas Perkawinan dan Kelahiran dalam Membangun Ketahanan Keluarga - Rosyada, Amrina (Al-Hukkam: Journal of Islamic Family Law, 2022)
The legality of marriage and the legality of birth are two interrelated elements, if a marriage does not have legality then it is not considered valid by the State, then if there are parties who feel disadvantaged, of course they cannot claim their rights in court. The absence of legality of birth also has implications for the validity of self-identity which is protected by the State. This thesis is the result of juridical-normative research that collects data through documentation studies. The results of the data that have been collected are then analyzed using content analysis methods. The results of this study indicate that: (1) in order to strengthen family resilience, the government requires every individual to register marriages so that their marriages are legalized in accordance with applicable laws and to register births to obtain a birth certificate as authentic evidence of a person's birth. (2) this policy is a form of implementation of Al-Maṣlaḥah Al-Mursalah in the category of mashlahah hajjiyah, because the policy regarding the legality of marriage and the legality of birth is an interest that is beneficial to the community and is a solution to the difficulties faced by the community.